The Piancatelli rearrangement of non-symmetrical furan-2, 5-dicarbinols for the synthesis of highly functionalized cyclopentenones. Issue 11 (22nd March 2021) - Cacheux, Fanny; Le Goff, Géraldine; Ouazzani, Jamal; Bignon, Jérôme; Retailleau, Pascal; Marinetti, Angela; Voituriez, Arnaud; Betzer, Jean-François
Abstract : Piancatelli rearrangement on substituted non-symmetrical furan-2, 5-dicarbinols has been developed using an effective combination of microwave activation and Lewis acid catalyst. Abstract : Substituted and non-symmetrical furan-2, 5-dicarbinols were readily prepared from hydroxymethylfurfural (HMF), a renewable raw material from biomass. The Piancatelli rearrangement of these furan-2, 5-dicarbinols, catalyzed by DyCl3 and under microwave activation, affords 5-substituted-4-hydroxymethyl-4-hydroxycyclopentenones in a regio- and diastereoselective manner. This methodology can be extended to aza-Piancatelli type reactions by using nitrogen nucleophiles, to furnish the corresponding aminocyclopentenone derivatives. These synthetized bis-hydroxylated cyclopentenone derivatives exhibited significant cytotoxicity against eight human tumor cell lines.